2024
DOI: 10.3390/su16010467
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder-Driven Policies and Scenarios of Land System Change and Environmental Impacts: A Case Study of Owyhee County, Idaho, United States

Li Huang,
Daniel Cronan,
Andrew (Anaru) Kliskey

Abstract: While stakeholder-driven approaches have been increasingly used in scenario modeling, previous studies have mostly focused on the qualitative elements, e.g., narratives and policy documents, from the stakeholders, but lack engagement of stakeholders with quantitative inputs. In this study, we conducted workshops with a stakeholder group to integrate the participatory mapping of future policies in the simulation, and to compare the environmental impacts after including the participatory mapping. A land system c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 117 publications
(179 reference statements)
0
1
0
Order By: Relevance
“…Adding policy constraints in the land use simulation can effectively limit the expansion of construction land in the region, especially protecting cropland and ecological land in and near the river area, thereby enhancing the credibility of the study. A study in Owyhee County, Idaho, USA, also found that conservation policies improved ecosystem services [62]. Additionally, compared with other studies [57,58,63], through finer land use classifications, this study can identify the multi-objective conflict problem of land use restructuring at the county scale.…”
mentioning
confidence: 72%
“…Adding policy constraints in the land use simulation can effectively limit the expansion of construction land in the region, especially protecting cropland and ecological land in and near the river area, thereby enhancing the credibility of the study. A study in Owyhee County, Idaho, USA, also found that conservation policies improved ecosystem services [62]. Additionally, compared with other studies [57,58,63], through finer land use classifications, this study can identify the multi-objective conflict problem of land use restructuring at the county scale.…”
mentioning
confidence: 72%